Simulation of Lightning Impulse on Surge Protection Device for Low Voltage System - Kamarudin, Muhammad Saufi; Mohd Fauzi, Nur Nadzirah Syazwani (Evolution in Electrical and Electronic Engineering, 2023)
Lightning strikes represent a dangerous threat to electrical equipment, especially for low-voltage alternating current (AC) systems. Overvoltage can be described as a condition when the suddenly rising voltage value happens more than the normal level of the protection devices rated. When a voltage rises above a certain level, the insulating system of electrical equipment and wires will flash over. In order to avoid flash over to happen, surge protection devices (SPDs) work as a crucial component for protecting such systems against transient overvoltages caused by lightning strikes to minimize damages or losses. This study focuses on identifying the effect of Metal Oxide Varistor (MOV) based on their type of protection modes; Normal Mode and Common Mode with the use of ATPDraw software. Heidler type of current sources are used to represent the lightning strikes that occur in the system with a standard current value of 8/20 µs. The circuit model constructed in this research was a three-phase low-voltage AC power system that is commonly used in residential areas. The system works by monitoring the lightning impulse transient on the MOV when a 10kA current is injected into the system. The MOV acts as an open circuit during normal conditions and in a short circuit condition when lightning surges occur to discharge the high current to the ground. The output waveform explained how the MOV works when lightning strikes happen and the amount of high current discharged to the ground in order to protect the system. By comparing the output response waveform for both types of protection modes, the normal mode gives more protection to the system compared to the common mode since the MOV is connected line-to-ground which tends to cause the system failure. It can be analyzed in detail for the capability of the MOV in handling the high current to avoid failures happening in the system depending on the burden that exists.